Comparison of the Gross Target Volumes Based on Diagnostic PET/CT for Primary Esophageal Cancer - Shi, Jingzhen; Li, Jianbin; Li, Fengxiang; Zhang, Yingjie; Guo, Yanluan; Wang, Wei; Wang, Jinzhi (Frontiers in Oncology, 2021)
Background Clinically, many esophageal cancer patients who planned for radiation therapy have already undergone diagnostic Positron-emission tomography/computed tomography (PET/CT) imaging, but it remains unclear whether these imaging results can be used to delineate the gross target volume (GTV) of the primary tumor for thoracic esophageal cancer (EC). Methods Seventy-two patients diagnosed with thoracic EC had undergone prior PET/CT for diagnosis and three-dimensional CT (3DCT) for simulation. The GTV3D was contoured on the 3DCT image without referencing the PET/CT image. The GTVPET-ref was contoured on the 3DCT image referencing the PET/CT image. The GTVPET-reg was contoured on the deformed registration image derived from 3DCT and PET/CT. Differences in the position, volume, length, conformity index (CI), and degree of inclusion (DI) among the target volumes were determined. Results The centroid distance in the three directions between two different GTVs showed no significant difference (P > 0.05). No significant difference was found among the groups in the tumor volume (P > 0.05). The median DI values of the GTVPET-reg and GTVPET-ref in the GTV3D were 0.82 and 0.86, respectively (P = 0.006). The median CI values of the GTV3D in the GTVPET-reg and GTVPET-ref were 0.68 and 0.72, respectively (P = 0.006). Conclusions PET/CT can be used to optimize the definition of the target volume in EC. However, no significant difference was found between the GTVs delineated based on visual referencing or deformable registration whether using the volume or position. So, in the absence of planning PET–CT images, it is also feasible to delineate the GTV of primary thoracic EC with reference to the diagnostic PET–CT image.